2016
DOI: 10.1080/10550887.2016.1177807
|View full text |Cite
|
Sign up to set email alerts
|

Gambling among European professional athletes. Prevalence and associated factors

Abstract: In Europe, the prevalence of gambling disorders in the general population ranges from 0.15 to 6.6%. Professional athletes are known for having risk factors for addictive behaviors, such as young age or sensation seeking, though no study has yet tried to evaluate the prevalence of gambling and gambling disorders among this specific population. The goals of this study were to estimate the prevalence of gambling, problematic or not, among European professional athletes and to explore the factors that are associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 60 publications
3
53
1
1
Order By: Relevance
“…The 8 percent occurrence is comparable to the figure reported in European team sports athletes (8 percent), measured with the same screening tool as in the present study but in almost exclusively male respondents [5], and elite athletes in various sports in Sweden (7 percent, measured instead with a three-item screening tool, the NODS-CLiP) [6,28]. The marked gender difference was also consistent with previous data in elite athletes; the present study did not demonstrate a likely increase in female problem gambling (one percent) compared to the general population, whereas the figure in men was 12 percent, comparable to the prevalence figure reported from elite athletes (14 percent, [6]) but clearly higher than that reported in Grall-Bronnec's study of team elite athletes, where almost 100 percent of participants were men [5].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The 8 percent occurrence is comparable to the figure reported in European team sports athletes (8 percent), measured with the same screening tool as in the present study but in almost exclusively male respondents [5], and elite athletes in various sports in Sweden (7 percent, measured instead with a three-item screening tool, the NODS-CLiP) [6,28]. The marked gender difference was also consistent with previous data in elite athletes; the present study did not demonstrate a likely increase in female problem gambling (one percent) compared to the general population, whereas the figure in men was 12 percent, comparable to the prevalence figure reported from elite athletes (14 percent, [6]) but clearly higher than that reported in Grall-Bronnec's study of team elite athletes, where almost 100 percent of participants were men [5].…”
Section: Discussionsupporting
confidence: 88%
“…Problem gambling was assessed as occurring at any time during lifetime, and measured through the two-item Lie/Bet scale, which includes one question about increased gambling (measuring the diagnostic criterion describing tolerance) and one question about having to lie to one's nearest family about the extent of one's gambling (corresponding to the diagnostic criterion describing lying), and where the endorsing of at least one item is interpreted as a positive screen for problem gambling [21][22][23]. The same instrument was also used in the study of problem gambling prevalence in European athletes cited above [5], allowing for comparison with the prevalence data of that study. The Lie/Bet instrument has been described to have a high sensitivity (0.81) and specificity (0.94) with respect to problem gambling as measured with the well-established Problem Gambling Severity Index in clinical mental health samples [24].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grall-Bronnec and colleagues,81 in their assessment of 1236 European professional athletes, reported that 56.6% of athletes had gambled during the previous year, with the prevalence of problem gambling being 8.2%, and with betting on one’s team, betting online and gambling regularly being associated with gambling problems. Betting on one’s team was specifically associated with current or past gambling problems.…”
Section: Introductionmentioning
confidence: 99%
“…Gambling disorder (GD) is a progressive and recurrent maladaptive pattern of gambling behavior, leading to impaired functioning. The prevalence of GD in the general population has been estimated between 1 and 2% in Western countries (Welte et al, 2008;Wardle et al, 2011), with several European countries reporting rates above 6% (Grall-Bronnec et al, 2016).…”
Section: Introductionmentioning
confidence: 99%